Updated Constraints on the Variations of the Fine-Structure Constant from an Analysis of White-Dwarf Spectra - T. D. Le (Symmetry, 2019)
I fused observed spectra from the white-dwarf star G191-B2B to constrain the spatial and temporal variation of the fine-structure constant, <semantics> α = e 2 4 π ε 0 ℏ c </semantics> . The analysis was combined with laboratory-measured and astronomically observed lines in [Ni V] to find <semantics> Δ α / α = ( − 0.003 ± 0.072 ) × 10 − 6 </semantics> . The obtained result allows a symmetry of the related comparison with previous studies looking for cosmological variations of <semantics> α </semantics> using spectra from Quasi Stellar Objects (QSOs). In this way, we can expect higher sensitivity from white-dwarf spectra than QSO spectra. Therefore, this study should have orders-of-magnitude higher sensitivity per system than previous quasar studies, and we should reduce statistical and systematic errors. The results of this study place a more stringent limit on <semantics> Δ α / α </semantics> than previous studies using the same data.